2016
DOI: 10.18203/issn.2455-4510.intjresorthop20162885
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of treatment of proximal tibial plateau fractures by minimally invasive percutaneous plating osteosynthesis technique

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong>Fractures of the proximal tibia are accompanied by a wide range of severity which may include stable undisplaced fractures with minimal soft tissue injury to highly comminuted unstable fractures, and severe soft tissue involvement. With the better understanding of fracture healing biology and biomechanics of fracture fixation and healing, the trend of treatment is towards biological fixation, which can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In 5 (14.70%) cases knee stiffness was observed. The average time for union of fractures was 19 weeks in Kancherla et al 15 series ranging from 16 to 24 weeks and an average of 121º knee joint range of motion was achieved. In J. Praneeth Kumar Reddy et al 16 study, most of these fractures were united by an average of 13.75 weeks ranging from 12 to 20 weeks and average range of motion was 114 degrees with only 1 patient (3.3%) had knee flexion of 90 degrees.…”
Section: Discussionmentioning
confidence: 96%
“…In 5 (14.70%) cases knee stiffness was observed. The average time for union of fractures was 19 weeks in Kancherla et al 15 series ranging from 16 to 24 weeks and an average of 121º knee joint range of motion was achieved. In J. Praneeth Kumar Reddy et al 16 study, most of these fractures were united by an average of 13.75 weeks ranging from 12 to 20 weeks and average range of motion was 114 degrees with only 1 patient (3.3%) had knee flexion of 90 degrees.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the management of high energy proximal tibia fractures is a challenging task, as they are often associated with a number of complications. Amongst the complications observed in the study of Kancherla NR et al 13 , 1 patient (5%) developed infection within 2 weeks postoperatively. Our results were comparable to the studies conducted by Egol KA et al 15 who reported no infection, Stannard JP et al 21 who reported 5.9% rate of infection and Cole PA et al 22 with infection rate of 4%.…”
Section: Section: Orthopaedicsmentioning
confidence: 88%
“…ORIF technique was used in 23 (76.7%) patients while MIPPO was used in 7 (23.3%) patients. Kancherla NR et al 13 did a prospective study on 20 patients with proximal tibial fractures. Most of the patients belonged to the age group of 20-40 years (75%), which were highly active and mobile age similarly in our study only 7 (23.3%) were treated with MIPPO technique.…”
Section: Intraoperative Factorsmentioning
confidence: 99%
See 2 more Smart Citations